Indus basin uniterrupted History of territory and politics from Alezander to Nehru - Sinha, Uttam Kumar (Gurgaon Penguin, 2021)
This book deals with history of terrorism and world politics.
Keywords: Indus Water Treaty; Foreign Relation-India and Pakistan; Water Treaty